Penerapan prinsip desain Daniel Libeskind pada fasilitas permainan tradisional Melayu Riau di Pekanbaru - Elza Fitria Ningsih; Yohannes Firzal; Pedia Aldy (Program Studi Arsitektur Fakultas Teknik Universitas Katolik Widya Mandira, 2020)
The deisgn of Riau Malay traditional games facility by adapting Daniel Libeskind’s design principle in Pekanbaru Pekanbaru City has a variety of children's attractions. The rides are generally found at malls or closed commercial centers that tend to provide modern games. Modern games are part of progressively advanced technological advances. Unlike the anciently, the children prefer to play by taking place on an empty field land. The condition of two different things between modern games and traditional games began to be characterized by increasingly many types of modern games and the loss of traditional games. The traditional game is a type of game originating from the Malay region of Riau. One of the game types is Congklak, Statak, gasing, and so on. Therefore, the title of the traditional game of Malay Riau that is useful to keep this traditional game can be preserved, especially children can play while learning to know the traditional values. With the concept of motion design in statak play, this facility is designed with its main function as a playground. It used the primary method of surveying, as well as the various literary sources and standards of game facilities as a secondary method. This traditional game facility emphasizes the design principle of Daniel Libeskind to create a modern design that remains thick with its traditional values. Although the facility design results have many geometric angles, but remain safe and do not interfere with children's movement. © 2020 Elza Fitria Ningsih, Yohannes Firzal, Pedia Aldy